The Others in Europe Legal and social categorization in context - Alarcon-Henriquez, Alejandra (European Studies, 2011)
This edited volume addresses the construction of identity classifications underlying the new forms of inclusion and exclusion that are to be found in contemporary Europe. Its scope covers practices of categorization and of resistance, both by majority groups.